Site-seeing: postcards of Palestine/Israel and the visual construction of place, 1890s to 1990s - Rogers, Seonaid M. (2019)
This PhD thesis explores postcards depicting Palestine/Israel in the period from 1890 – 1990, from the archives of the British Museum and comparable collections, to analyse the ways in which commercial visual media of this type reflected, and at times shaped, national narratives and identit(ies). It also examines the interrelations between the postcards and wider visual culture by looking at motifs featured on postcards and imagery in contemporaneous newspaper and travel photography, posters, and advertisements. I argue that postcards are an understudied visual medium when discussing the formation of national narratives and place-making, and that while they often repeat the same sights and generic landscapes, they function as unique commercial objects for single purchase, which commodify political and ideological positions and sites for the tourist gaze.